The Stickiness of Selling, General, and Administrative Costs in the Indonesian Companies - Armanto, Benny; Tiono, Karoline Melanika; Suthiono, Henry (International Research Journal of Business Studies, 2014)
Selling, general and administration costs are the main components in the Income Statement. A large number of permanent staff in sales and marketing department will make the company dominated by the fixed costs. This fact could lead to sticky cost behavior. In addition, role of the manager can also cause the cost stickiness. When the company’s revenue decreases, manager may delay to decrease the cost or not even decrease cost at all. The objective of the study is to determine whether cost stickiness of selling, general and administrative in the Indonesian listed companies. This study applied log-linear data panel regression with 3605 firm years that is listed in Indonesian Stock Exchange (BEI) from 1993 – 2013. This study finds that selling, general, and administrative costs are sticky only for the manufacturing companies. Furthermore, the results show that adjustment of sales, general, and administrative costs delayed by the manager when revenue decreases, yet the cost stickiness will be reduced in the next period.